STRATEGI PEMERINTAH DALAM MENGENDALIKAN ANGKA KEMISKINAN DI DINAS SOSIAL KABUPATEN BANTAENG - Novianti, Fitri; Ma"ruf, Adnan; Arni, Arni (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
Poverty is an economic phenomenon that has become a serious issue that must be addressed immediately. This phenomenon is a serious problem not only in Indonesia but also worldwide. The aim of this research is to identify the strategies used by the government of Bantaeng Regency to control poverty rates.This study employs a qualitative approach using observation, interviews, and documentation methods. The research findings reveal that the poverty rate in Bantaeng Regency was initially at 8%, then increased to 9% after the Covid-19 pandemic before dropping back to 8%, with fluctuations that were not too significant. According to the Social Affairs Office of Bantaeng Regency, the factors contributing to poverty include the Covid-19 outbreak, education level, low income, lack of skills, stagnant mindset, inadequate healthcare, and economic uncertainty. The government's strategy for controlling poverty in Bantaeng Regency includes social assistance programs and improving human resource quality through education. Social assistance helps the economic development of the community by ensuring their basic needs are met, and the aid provided can serve as capital for starting businesses. Meanwhile, enhancing human resource quality through education helps improve people's skills in various fields. Based on the data obtained, the implementation of these strategies has successfully controlled the poverty rate in Bantaeng Regency.